(untitled) (Global Journal of Human-Social Science, 2021)
This article derived from a doctoral thesis analyzes the way in which some clientelist practices of sectors of the traditional political elite and the actions of illegal armed actors drug trafficking groups FARC-EP paramilitaries ELN and GAO have carried out co-optation processes in front of to political participation in Colombia and more specifically in the 30 municipalities that make up the Magdalena Medio region which is located between the departments of Antioquia Santander Bol var and Cesar